THE “GENERAL SCHOOL EDUCATION INTRODUCTORY ENGLISH CURRICULUM FOR GRADE 1 AND GRADE 2”: A NEW INNOVATION IN FOREIGN LANGUAGE GENERAL SCHOOL EDUCATION IN VIETNAM - Van, Hoang Van (VNU Journal of Foreign Studies; Vol 36 No 4DO - 10.25073/2525-2445/vnufs.4570, 2020)
This paper is concerned with a new innovation in foreign language general school education in Vietnam which has been attracting considerable attention from Vietnamese foreign language educators, foreign language teachers, and the general public – the General School Education Introductory English Curriculum for Grade 1 and Grade 2 issued in 2018 by the Ministry of Education of Vietnam. To highlight this important innovation, the paper attempts to address three main issues: (1) it will examine and clarify some of the most important aspects of the General School Education Introductory English Curriculum for Grade 1 and Grade 2 ; (2) it will present and discuss in some detail the contents in Tiếng Anh 1 (English 1) – a new English textbook developed in accordance with the General School Education Introductory English Curriculum for Grade 1 and Grade 2 by Vietnam National Publishing House in collaboration with Springer Nature Macmillan Education; and (3) it will outline and discuss some specific classroom methods and present a new procedure for teaching an activity/task to help teachers and pupils teach and learn English effectively.